Agro-industrial residue gasification feasibility in captive power plants: A South-Asian case study - Naqvi, S.R. (Elsevier Ltd, 2021)
The objective of this study is to build knowledge on the potential of agro-industrial residue gasification (AIRG) for use in captive power generation through a comprehensive case study. In order to evaluate the economic viability, key performance indicators, such as net present value (NPV), levelized cost of electricity (LCOE), and operating costs etc. are studied. The major textile industry located in the Raiwind area of Punjab province of Pakistan has been selected. The effect and variations of the capacity factor has also been studied coupled with the levelized cost of electricity. The agricultural residue as feedstock to the gasifier is rice husk that is the abundantly available in South Asia. Furthermore, the impact of government subsidies on natural gas is also under the scope of the study. The agro-industrial residue gasification system is found to be a potential alternative to furnace oil (FO) or gas-based captive power plants (CPPs). The results of residue-based gasification system imply a large potential when comparing the cost of electricity with national grid electricity during the peak hours. Therefore, the proposed gasification system offers economic incentives when the textile industry potentially utilizes gasification-based electricity during peak hours and national grid electricity during off-peak hours. Â© 2020 Elsevier Ltd